2017
DOI: 10.1038/bmt.2016.347
|View full text |Cite|
|
Sign up to set email alerts
|

Cotransplantation of bone marrow-derived mesenchymal stem cells in haploidentical hematopoietic stem cell transplantation in patients with severe aplastic anemia: an interim summary for a multicenter phase II trial results

Abstract: Haploidentical hematopoietic stem cell transplantation (haplo-HSCT) for severe aplastic anemia (SAA) is mainly limited by the high incidence of graft failure and GvHD. Mesenchymal stem cells (MSCs) have been shown to support hematopoiesis in vivo and to display potent immunosuppressive effects to prevent or treat GvHD after HSCT. In a multicenter phase II trial, we developed an approach with co-transplantation of MSCs in patients undergoing haplo-HSCT. Forty-four patients with SAA were included. The conditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
4
45
2
Order By: Relevance
“…This study showed that MSCs support in vivo Alternative Immune-Mediated-Based Methods in the Aplastic Anemia Treatment DOI: http://dx.doi.org /10.5772/intechopen.89090 normal hematopoiesis and display potent immunosuppressive effects. The other metacentric study shows that cotransplantation of BM-MSCs and haplo-HSCT could reduce the risk of graft failure and severe GVHD in SAA [104]. Similar data were obtained in a study that used cotransplantation of haploidentical HSCs and BM-MSCs into children with SAA without an HLA-identical sibling donor.…”
Section: Clinical Studies With Msc In Combination To Hsct Transplantasupporting
confidence: 64%
“…This study showed that MSCs support in vivo Alternative Immune-Mediated-Based Methods in the Aplastic Anemia Treatment DOI: http://dx.doi.org /10.5772/intechopen.89090 normal hematopoiesis and display potent immunosuppressive effects. The other metacentric study shows that cotransplantation of BM-MSCs and haplo-HSCT could reduce the risk of graft failure and severe GVHD in SAA [104]. Similar data were obtained in a study that used cotransplantation of haploidentical HSCs and BM-MSCs into children with SAA without an HLA-identical sibling donor.…”
Section: Clinical Studies With Msc In Combination To Hsct Transplantasupporting
confidence: 64%
“…In addition, recent advances in conditioning regimen, prophylaxis of graft-vs-host disease (GVHD), and supportive care have significantly enhanced therapeutic benefits of HRD-HSCT. More importantly, different centers in China including our center have reported the feasibility and promising outcomes of using HRD-HSCT in patients with acquired SAA, achieving long-term OS of 77.3%-86.1%, [5][6][7][8] which is comparable to outcomes of patients with SAA receiving HLA-identical sibling HSCTs. 8 Furthermore, a recent finding suggests that HRD-HSCT has similar efficacy in the treatment of pediatric SAA compared to IST.…”
mentioning
confidence: 66%
“…The MSC sources were bone marrow (BM, n = 12 studies) and umbilical cord (UC, n = 4 studies), the majority of them from a different donor than HSCT. For most studies, a single dose of MSC was administered on the same day than HSCT while in 4 studies, a second dose of MSC was also administered on day + 2 [25], + 14 [26,27] or + 21 [28] after HSCT. In two studies, the single administration of MSC was carried out after HSCT, on day + 28 (19-54) [29] or after more than 4 months after transplantation [30].…”
Section: Mesenchymal Stromal Cells For the Prevention Of Gvhd In Patimentioning
confidence: 99%
“…Data from five and seven studies showed no differences in OS (P = 0.74, Figure S22A) and response rates between patients with aGvHD and cGvHD infused with MSC, although patients that suffered cGvHD were less likely to achieve OR (0.77; 95% CI, 0.56-1.06, Figure S22B) and CR (0.66; 95% CI, 0.32-1.36, Figure S22C) than aGvHD patients (see Additional file, pp. [26][27].…”
Section: Mesenchymal Stromal Cells For the Treatment Of Steroidrefracmentioning
confidence: 99%